2002
DOI: 10.1200/jco.2002.12.063
|View full text |Cite
|
Sign up to set email alerts
|

DPC4/Smad4 Expression and Outcome in Pancreatic Ductal Adenocarcinoma

Abstract: Tumor size (> 45 mm), resection margin involvement, and perineural invasion were independent prognostic factors. Preoperative assessment of DPC4/Smad4 expression has potential as a prognostic indicator in patients with PC since resection did not benefit those patients whose cancers expressed DPC4/Smad4 and accurate assessment of DPC4/Smad4 expression, unlike tumor size, margin status, and perineural invasion, does not require resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
3
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 31 publications
9
101
3
4
Order By: Relevance
“…There have also been several reports of various biological markers that may carry some prognostic significance. These include growth factors such as vascular endothelial growth factor and platelet-derived endothelial cell growth factor (Fujimoto et al, 1998), microsatellite instability (Nakata et al, 2002), tumour suppression gene expression such as SMAD4 (Biankin et al, 2002) and the expression of mutated genes controlling response to DNA damage, such as GADD45a and p53 (Yamasawa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several reports of various biological markers that may carry some prognostic significance. These include growth factors such as vascular endothelial growth factor and platelet-derived endothelial cell growth factor (Fujimoto et al, 1998), microsatellite instability (Nakata et al, 2002), tumour suppression gene expression such as SMAD4 (Biankin et al, 2002) and the expression of mutated genes controlling response to DNA damage, such as GADD45a and p53 (Yamasawa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We identified a cohort of 128 patients with a diagnosis of pancreatic adenocarcinoma that underwent pancreatic resection or biopsy between January 1972 and November 2001 with available archived tissue. This cohort represents a subset of a previously described group of 348 patients (28). Archival formalin-fixed, paraffin-embedded tissue from all 128 pancreata that were resected or biopsied were used to construct seven pancreatic cancer tissue arrays, which contained up to 55 Â 1.6 mm cores per slide.…”
Section: Methodsmentioning
confidence: 99%
“…47 P21 CIP1 overexpression is also a very early event in pancreatic neoplastic PanIN lesions, even before the aberrant expression of p53, cyclin D1, and DPC/Smad4 starts. 48 In pancreatic acinar cells it has been shown that p48/Ptf1 is directly responsible for growth suppression via transcriptional activation of p21 CIP1 30 . In that situation, p21 CIP1 thus functions as a cell-cycle inhibitory protein.…”
Section: 3mentioning
confidence: 99%